Hydrologic erosion and redistribution of ¹³⁷Cs following fire at semiarid sites - Johansen, Mathew P., author; Ibrahim, Shawki, A., advisor; Whicker, F. Ward, committee member; Hakonson, Thomas E., committee member; Ascough, James C., II, committee member (Colorado State University. Libraries, 2002)
Of the few natural processes that reconcentrate dispersed environmental contaminants, landscape fire stands out as having potential to rapidly reconcentrate and redistribute contaminants, and do so on large scales. This study was conducted to quantify changes in concentration of a widely dispersed environmental contaminant –fallout 137Cs– in soils and runoff following landscape fires. Measurement of changes in fallout 137Cs concentration after fire was conducted in grassland, shrubland, and forest ecosystems. At each site, burned and unburned plots (3.0 x 10.7m) were subjected to simulated rainstorms using a 16m rotating-boom rainfall simulator. Burned conditions ranged from a controlled, low-severity fire in grassland, to a high-severity wildfire in ponderosa pine forest A series of reconcentration and redistribution processes occur during and after fire. Ashing of biomass during fire resulted in elevated 137Cs concentrations in burned soils, from 46% in grassland to about 300% higher in ponderosa forest where large amounts of ash were deposited. After fire, 137Cs concentrations in runoff from burned plots were elevated one order of magnitude higher than in runoff from unburned plots, and two orders of magnitude higher in post-fire runoff from a small watershed. The greatest surface water transport of 137Cs from plots, up to 11.6 KBq ha-1 per mm rainfall, occurred after severe burning in ponderosa pine forest where up to 80% vegetation cover was removed compared to yields from grassland and shrub land that were an order of magnitude less. 137Cs increases in runoff were associated with increased sediment transport after fire, and, further, these sediments were enriched in 137Cs by factors ranging from 1.4 to 2.9 compared to parent soils. However, enrichment ratios (137Cs in runoff sediments compared to parent soils) were not affected by burning. Study results provide evidence of order of magnitude increases in reconcentration and redistribution of a sorbed contaminant following fire that has relevance to a wide range of ecosystem dynamics, geophysical, fire management, and risk assessment studies.
Keywords: environmental engineering; hydrology; hydrologic sciences